تعارض و رفعِ تعارض کے متعلق حنفی مذہب کی تحقیق - محمد مشتاق احمد (FIKR-O NAZAR فکر ونظر, 2013)
Some renowned hanafi jurists of the latter period have asserted that in case of a conflicting legal evidences (adillah), the hanafi School first opts for abrogation (naskh), failing which it goes for preference (tarjih) and finally it tries reconciliation (jam‘). This view has generally been accepted by the modern scholars. However, a thorough review of the classical manuals of the Hanafi School, both on legal theory (usul al-fiqh) as well as law (fiqh) reveals that this view does not accurately represent the hanafi methodology for resolving conflicts. The present paper explores the hanafi manuals to accurately determine the hanafi methodology and also to find out the reasons which led the later hanafi jurists to present a different picture. For this purpose, it compares the position of